Implementing dialogic communication for complaint management in Malang Private Hospital, Indonesia - Arizona, Yohana Kartika; Wulandari, Maulina Pia (Faculty of Communications Science, Dr. Soetomo University, 2026)
Persistent increases in patient complaints in private hospitals indicate a structural gap in how complaint management systems integrate dialogic communication principles in practice. This mixed-method study examined the implementation of a dialogic communication framework in managing patient complaints at a private hospital in Malang, Indonesia. This study particularly focused on how the current complaint system reflects the principles of mutuality, transparency, and organisational commitment. This study integrated in-depth interviews with key stakeholders and a quantitative analysis of 605 patient complaints. The findings indicate a fractured dialogue that demonstrates a substantial gap between the procedurally and performatively responsive complaint system and its actual capacity for genuine dialogic communication. This management misconduct is rooted in systemic fragmentation, sectoral ego, and an organisational unwillingness to embrace the risk of transparency. Ultimately, this study proposes the Integrated Public Service Communication Flow model, designed to shift the organisational culture from a reactive and monologic approach to a proactive, relational, and genuinely dialogic. This proposed model accentuates a concrete framework for rebuilding patient trust by embedding mutuality and commitment into the hospital operations.